Considerations on the Setting of Cervantes’s Captivity Narratives - Jae Won Chang (Humanities, 2024)
This study aims to explore the issues of Islamophobia and Christian ideology prevalent in Spanish society in the 16th and early 17th centuries by examining the slave trade conducted by Barbary corsairs and the hard lives of Christian captives depicted in the literary works of Miguel de Cervantes, and to highlight his efforts to overcome the clash of civilizations between Christianity and Islam. To achieve this goal, first, the study delves into the historical context of the clash between Spain and Islam in the Mediterranean during the 16th century. Cervantes, who took part in the Battle of Lepanto in 1571, was captured by Barbary corsairs on his return from military service and spent five years as a captive in the Bagnio of Algiers. The painful experience left indelible marks on his works. This study focuses on the dual meaning of Orientalism in his works. One prevalent form of Orientalism in Spain and Europe during that period portrayed Muslims as barbaric and anti-Christian. However, Cervantes presented an alternative Orientalism to propose a pathway to co-existence, rather than conflict, between civilizations and religions. Therefore, this study explores how Cervantes, even though he himself was a victim of the clash of civilizations, sought to overcome the confrontations and conflicts in his works, rather than perpetuating the prevalent Islamophobia of his time.